2013
DOI: 10.1136/oemed-2013-101735
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of exposure assessment approaches: lung cancer and occupational asbestos exposure in a population-based case–control study

Abstract: It is generally assumed by epidemiologists that self-reported exposure assessments result in inflated risk estimates. In this study, self-reports found no association with a well-established risk factor, whereas a high-quality job-exposure matrix revealed relative risk estimates that are more consistent with previous findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…This present study found a significant association between the duration of asbestos exposure measured in years and the risk of lung cancer that supported the results from previous studies [19,23]. This association is slightly weaker as it does not take the intensity into account.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This present study found a significant association between the duration of asbestos exposure measured in years and the risk of lung cancer that supported the results from previous studies [19,23]. This association is slightly weaker as it does not take the intensity into account.…”
Section: Discussionsupporting
confidence: 91%
“…We observed that the chance of getting lung cancer more than doubled among exposed subjects compared with unexposed subjects and it was comparable to the findings of Hardt et al [19]. In their case-control study, those who were grouped as exposed subjects by DOM-JEM assessment had an odds ratio of 1.9 (95% CI = 1.3-2.7) compared to those with no exposure.…”
Section: Discussionsupporting
confidence: 89%
“…Numerous ways were developed to estimate the occupational exposure (self assessment, job titles, lenghts of exposure, specific occupational task, job-exposure matrix) [5,6]. In our cases, exposure assessment was based on the documentation provided by the past employer and on expert evaluation of the job risk.…”
Section: Resultsmentioning
confidence: 99%
“…However, we have no reason to believe that recall of jobs associated with exposure to mineral oils would have been biased in any way. Although job-exposure matrices in themselves have limitations, they remain the only feasible approach to exposure assessment for studies of this size, containing over 35 000 jobs 39. In this study, we used a job exposure matrix (INTEROCC JEM) that was based on the FINJEM.…”
Section: Discussionmentioning
confidence: 99%